Effectiveness of blended learning to improve medical students’ communication skills: a randomized, controlled trial - Sebastian Gross; Kurt Wunderlich; Armon Arpagaus; Christoph Becker; Flavio Gössi; Benjamin Bissmann; Samuel K. Zumbrunn; Michael Wilde; Sabina Hunziker (BMC Medical Education)
Abstract Background This study aimed to evaluate whether a blended learning course improves medical students’ communication skills compared to a face-to-face only lecture. Methods After completing a face-to-face lecture on communication skills, 2nd year medical students were gender-matched and randomized to either an intervention receiving an interactive video-based online learning module covering the content of the previous lecture and including a knowledge assessment or a control group only receiving a knowledge assessment. The primary endpoint was students’ knowledge about communication techniques assessed by a predefined score from 0 to 100. Secondary outcomes included students’ feedback and satisfaction on a scale from 0 to 5. Additionally, qualitative analysis of free-text responses to patient case vignettes was conducted. Results One hundred sixty-four medical students were included in the final analysis (64% female). The intervention group had significantly higher knowledge (mean, SD points) (73.6 ± 10.7 versus 56.7 ± 15.3, adjusted difference 17.02, 95%CI 12.95 to 21.1, p < 0.001) and reported higher satisfaction (4.3 ± 0.9 versus 3.5 ± 1.0, difference 0.78, 95%CI 0.48 to 1.07, p < 0.001) compared to the control group. Qualitative analysis of free-text responses also revealed improvements in patient-centered communication techniques in the intervention group. Conclusions Blended learning significantly enhances medical students’ communication skills and satisfaction compared to traditional lecture-based learning and may thereby contribute to the development of future knowledge and practices to improve patient-centered care. Clinical trial number Not applicable.